MANAJEMEN KURIKULUM TAHFIDZUL QUR’AN DI PONDOK PESANTREN TAHFIDZUL QUR’AN ANAK (PTYQA) KUDUS - Ahmad Amirul Wildan (STIT Bustanul 'Ulum Lampung Tengah, 2025)
The increasing demand for early-age Qur’anic memorization programs in Indonesia has led to the emergence of child-focused tahfidz institutions, yet systematic studies on curriculum management in such contexts remain limited. This study aims to explore the curriculum management practices of Tahfidzul Qur’an in Pondok Pesantren Tahfidzul Qur’an Anak (PTYQA) Kudus, a prominent pesantren that has produced hundreds of child huffadh through a structured six-year program. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, participatory observation, and institutional document analysis. The findings reveal that curriculum planning at PTYQA integrates traditional Islamic educational values with professional management strategies, especially through the application of the Yanbu’a method. Curriculum implementation emphasizes individualized instruction based on initial student reading abilities and a highly disciplined learning schedule, while evaluation involves regular formative assessments and internal supervision. However, summative evaluation of alumni outcomes remains limited. The study concludes that PTYQA has established a hybrid curriculum management model that is pedagogically sound, spiritually grounded, and contextually adaptive to the developmental needs of children. These findings contribute a new perspective to Islamic education literature by highlighting the managerial and pedagogical dimensions of tahfidz education for children, suggesting future research on outcome-based curriculum models and professional development for tahfidz teachers.